Claudine at st clare's - Blyton,Enid (London: Egmont UK Ltd, 1905)
In the book the twins are back at st clares for the summer term. There is a girl called Carlotta who used to be a circus girl and sneaky Prudence tells the class expecting them to hate her but the class love Carlotta. Another girl called Sadie is nearly kidnapped but Carlotta saves her.